Endotoxin tolerance and trained immunity: breaking down immunological memory barriers - López-Collazo, Eduardo; del Fresno, Carlos (Frontiers in Immunology, 2024)
For decades, innate immune cells were considered unsophisticated first responders, lacking the adaptive memory of their T and B cell counterparts. However, mounting evidence demonstrates the surprising complexity of innate immunity. Beyond quickly deploying specialized cells and initiating inflammation, two fascinating phenomena – endotoxin tolerance (ET) and trained immunity (TI) – have emerged. ET, characterized by reduced inflammatory response upon repeated exposure, protects against excessive inflammation. Conversely, TI leads to an enhanced response after initial priming, allowing the innate system to mount stronger defences against subsequent challenges. Although seemingly distinct, these phenomena may share underlying mechanisms and functional implications, blurring the lines between them. This review will delve into ET and TI, dissecting their similarities, differences, and the remaining questions that warrant further investigation.